Offside decision making of assistant referees in the English Premier League: Impact of physical and perceptual-cognitive factors on match performance - Catteeuw, P.; Gilis, B.; Wagemans, J.; Helsen, W. (Journal of Sports Sciences, 2010)
In the present study, we investigated the accuracy of offside judgements of assistant referees in the English Premier League. The moment in the match, the position and movement speed of the assistant referee, attacker and second-last defender, together with the angle of view for the assistant referee were all considered to underlie incorrect decisions. The error rate was 17.5% (868 of 4960 situations). As the English assistant referees tended not to signal in doubtful situations (c = 0.91), there was an overall bias towards non-flag errors (773 non-flag errors vs. 95 flag errors). The flash-lag hypothesis could explain all flag errors, whereas the optical-error hypothesis could explain a proportion of the non-flag errors (45.4%). Fatigue, movement speed, and angle of view did not have a detrimental effect on offside decision making. In conclusion, there were fewer flag errors than in the 2002 and 2006 FIFA World Cups, whereas the number of non-flag errors rose. The increased awareness of factors involved in offside decision making and the instructions to give the benefit of the doubt to attackers could have contributed to this situation.